The Role of Communicative Tasks in Training Students the Foreign Language Usage in Professional Activity. - Бородина, А. И.; Скиданова, Н. В. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2016)
The article deals with the possibilities of using communicative tasks to develop skills which are necessary to work with the text as a source of information. Patterns of creative tasks in all aspects of foreign language teaching are presented, their efficiency is substantiated. Examples of tasks corresponding to the situations of professional communication in a foreign language are given.